2015
DOI: 10.1080/21645515.2015.1094594
|View full text |Cite
|
Sign up to set email alerts
|

Tdap vaccine attitudes and utilization among pregnant women from a high-risk population

Abstract: Infants infected with Bordatella pertussis experience high morbidity and significant mortality. Vaccinating pregnant mothers with the tetanus-diphtheria-acellular pertussis (Tdap) vaccine is a recommended strategy for preventing infant pertussis. This is especially important for mothers living in poverty and from racial and ethnic minority populations as these groups are at increased risk of having a pertussis-affected infant. Using the Health Belief Model as a framework, we surveyed a convenience sample of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 32 publications
0
34
0
Order By: Relevance
“…Another important finding was that pregnant women of ethnic minorities were significantly less likely to accept vaccination than those identifying as 'White British'. Previous research has similarly demonstrated lower vaccine acceptance among these groups [23][24][25] , and these findings highlight the importance of taking into account possible cultural/religious and language barriers when counselling these women and producing educational materials. The underlying reasons for the difference in vaccine attitudes between ethnic groups remains a significant gap in our knowledge, and future studies in this specific area are needed.…”
Section: A C C E P T E Dmentioning
confidence: 55%
“…Another important finding was that pregnant women of ethnic minorities were significantly less likely to accept vaccination than those identifying as 'White British'. Previous research has similarly demonstrated lower vaccine acceptance among these groups [23][24][25] , and these findings highlight the importance of taking into account possible cultural/religious and language barriers when counselling these women and producing educational materials. The underlying reasons for the difference in vaccine attitudes between ethnic groups remains a significant gap in our knowledge, and future studies in this specific area are needed.…”
Section: A C C E P T E Dmentioning
confidence: 55%
“…Lack of conversation with a healthcare professional about influenza and pertussis vaccination in pregnancy has been identified as a barrier to vaccination in previous original research into vaccine hesitancy [51][52][53]. Survey data has found that 16 -24 per cent of women had a meaningful discussion with their GP about pertussis vaccination in pregnancy [54,55].…”
Section: Staff Education and Trainingmentioning
confidence: 99%
“…It has been suggested that women may decline vaccination due to a lack of information and awareness [54]. Additionally, safety concerns have been identified as a barrier for vaccination in pregnancy [19,52,55] despite extensive research into vaccine safety [2,10]. Qualitative evidence from London suggests that many mothers trust the NHS and if the NHS are providing vaccination, they are more likely to trust the vaccine [51].…”
Section: Information and Education For Patientsmentioning
confidence: 99%
“…Maternal attitudes are remarkably consistent; their primary concern is that the vaccine is safe both for them and their baby, and they desire sufficient discussion with their provider to explain the rationale behind immunization. 83,84,[86][87][88][89] The benefits of and likely acceptance by pregnant women of pertussis vaccination has resulted in strong statements in support from organizations such as the American College of Obstetricians and Gynecologists, along with resources such as the Tdap toolkit, which provides literature and talking points for providers. 90,91 While these interventions have not as yet been translated into robust uptake rates, at least at a national level in the US, they address some of the provider level barriers.…”
Section: Implementation Of Maternal Immunizationmentioning
confidence: 99%
“…Studies show that 78% to 93% of pregnant or postpartum women say they would receive a vaccine recommended by their provider, regardless of influence from other sources such as family, friends or online resources. [83][84][85][86][87][88][89] Numerous studies have evaluated the attitudes of pregnant and postpartum women toward maternal immunization. Although some cultural differences exist, themes are emerging.…”
Section: Implementation Of Maternal Immunizationmentioning
confidence: 99%